PRELIMINARY RESULT FOR THE Sm-Nd WHOLE-ROCK AGE OF THE METAMORPHIC ROCKS FROM MOUNT PARDOE IN THE NAPIER COMPLEX, EAST ANTARCTICA - タイノショウ, ヨシアキ; カガミ, ヒロオ; タカハシ, ユウヘイ; イイズミ, シゲル; オサナイ, ヤスヒト; ツチヤ, ノリヨシ; TAINOSHO, Yoshiaki; KAGAMI, Hiroo; TAKAHASHI, Yuhei; IIZUMI, Shigeru; OSANAI, Yasuhito; TSUCHIYA, Noriyoshi (National Institute of Polar Research, 1994)
P(論文) The Sm-Nd whole rock isochron age was determined for metamorphic rocks from Mount Pardoe, Napier Complex. Acidic gneiss (orthopyroxene-mesoperthite-quartz gneiss), being one of the main representative metamorphic rocks, gave an age of 2516±274 Ma with an initial ^<143>Nd/^<144>Nd ratio of 0.50914±0.00021. εNd values normalized to 2516 Ma for individual acidic gneiss range from -3.7 to -7.0. This Sm-Nd whole-rock isochron age indicates a major period of equilibration of the isotopic system on a whole-rock scale at 2516±274 Ma. departmental bulletin paper